Computer literacy among first year medical students in a developing country: A cross sectional study - Ranasinghe, P.; Wickramasinghe, S.A.; Pieris, W.A.R.; Karunathilake, I.M.; Constantine, G.R. (BMC Research Notes, 2012)
Background: The use of computer assisted learning (CAL) has enhanced undergraduate medical education. CAL improves performance at examinations, develops problem solving skills and increases student satisfaction. The study evaluates computer literacy among first year medical students in Sri Lanka. Methods: The study was conducted at Faculty of Medicine, University of Colombo, Sri Lanka between August-September 2008. First year medical students (n = 190) were invited for the study. Data on computer literacy and associated factors were collected by an expert-validated pre-tested self-administered questionnaire. Computer literacy was evaluated by testing knowledge on 6 domains; common software packages, operating systems, database management and the usage of internet and E-mail. A linear regression was conducted using total score for computer literacy as the continuous dependant variable and other independent covariates. Results: Sample size-181 (Response rate-95.3%), 49.7% were Males. Majority of the students (77.3%) owned a computer (Males-74.4%, Females-80.2%). Students have gained their present computer knowledge by; a formal training programme (64.1%), self learning (63.0%) or by peer learning (49.2%). The students used computers for predominately; word processing (95.6%), entertainment (95.0%), web browsing (80.1%) and preparing presentations (76.8%). Majority of the students (75.7%) expressed their willingness for a formal computer training programme at the faculty. Mean score for the computer literacy questionnaire was 48.4 ± 20.3, with no significant gender difference (Males-47.8 ± 21.1, Females-48.9 ± 19.6). There were 47.9% students that had a score less than 50% for the computer literacy questionnaire. Students from Colombo district, Western Province and Student owning a computer had a significantly higher mean score in comparison to other students (p < 0.001). In the linear regression analysis, formal computer training was the strongest predictor of computer literacy (β = 13.034), followed by using internet facility, being from Western province, using computers for Web browsing and computer programming, computer ownership and doing IT (Information Technology) as a subject in GCE (A/L) examination. Conclusion: Sri Lankan medical undergraduates had a low-intermediate level of computer literacy. There is a need to improve computer literacy, by increasing computer training in schools, or by introducing computer training in the initial stages of the undergraduate programme. These two options require improvement in infrastructure and other resources.
Keywords: Computer literacy; Medical undergraduates; Sri Lanka; Developing country